2022
DOI: 10.1007/s43979-022-00038-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of heat pump in heating decarbonization for China carbon neutrality

Abstract: Heating decarbonization is a major challenge for China to meet its 2060 carbon neutral commitment, yet most existing studies on China’s carbon neutrality focus on supply side (e.g., grid decarbonization, zero-carbon fuel) rather than demand side (e.g., heating and cooling in buildings and industry). In terms of end use energy consumption, heating and cooling accounts for 50% of the total energy consumption, and heat pumps would be an effective driver for heating decarbonization along with the decarbonization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Emission evaluation: reproduced with permission. 23 Copyright 2022 Springer Nature. Economic evaluation: reproduced with permission.…”
Section: Interdisciplinary Research Effortsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emission evaluation: reproduced with permission. 23 Copyright 2022 Springer Nature. Economic evaluation: reproduced with permission.…”
Section: Interdisciplinary Research Effortsmentioning
confidence: 99%
“…Copyright 2021 Elsevier. Emission evaluation: reproduced with permission 23. Copyright 2022 Springer Nature.…”
mentioning
confidence: 99%
“…Other studies have demonstrated the clear air quality and public health benefits from heat pump adoption in China (Liu & Mauzerall, 2020; Zhou et al, 2022). Heat pumps have also been shown to have significant potential to contribute to China's carbon neutrality goals (Yan et al, 2022).…”
Section: Policy Barriers To Heat Pump Adoptionmentioning
confidence: 99%
“…The next phase of the transition is likely to require greater attention to demand-side energy efficiency and electrification of energy consumption. To this end, heat pumps have an important role in decarbonizing the heating sector in China (Yan et al, 2022). This is particularly true in rural areas, where heating historically has relied on fossil fuels, and where policy maker focus on air quality combined with rising incomes and changing preferences for interior comfort and indoor air quality are leading to rapidly rising energy demand for clean space heating (Tang et al, 2021).…”
Section: Introduction: China's Distributed Energy and Clean Heating T...mentioning
confidence: 99%
“…Depending on the climate it is possible to replace the boiler with an air to water heat pump (in warmer climates) or to couple the high temperature heat pump with the natural gas boiler (in colder climates). While in literature the replacement of traditional boilers considering the national scale is analyzed in Italy as a whole [1,2] and similarly in other individual countries [3,4,5], or even for groups of nations [6,7] or for the European Union as a whole [8,9], there are not specific works on the numerical detail of each region. For this reason, the primary objective of the present work is to identify for all territorial units both the energy values which can be supplied by heat pumps to replace fossil fuel-fired boilers for heating buildings, and the demand for electricity necessary for the operation of heat pumps and finally the net energy saved by that replacement.…”
mentioning
confidence: 99%